Resolving atomistic structure and oxygen evolution activity in nickel antimonates. Issue 10 (31st January 2023) - Rao, Karun K.; Zhou, Lan; Lai, Yungchieh; Richter, Matthias H.; Li, Xiang; Lu, Yubing; Yano, Junko; Gregoire, John M.; Bajdich, Michal
Abstract : Identification of the crystal structure of novel Ni–Sb–O catalyst for oxygen evolution reaction. Calculated properties consistent with experimentally measured photoactivity and resistance to corrosion. Abstract : The oxygen evolution reaction (OER) requires electrodes that are not only catalytically active, but also stable under harsh electrochemical environments to enable efficient, durable technologies. Our recent report of a stable amorphous Ni0.5 Sb0.5 O z OER photoanode established Ni–Sb–O as an important system for computational understanding of both the structural and catalytic behavior of these complex oxides. In the present work we show that Ni x Sb1− x O z with x > 0.33 crystallizes into a previously unknown phase. Guided by experimental X-ray diffraction, we use density functional theory calculations to perform a prototype phase search to identify a broad family of stable and metastable mixed rutile and hexagonal-like phases for x = 0.33, 0.50, and 0.66 compositions. For the identified phases, we predict favorable oxygen vacancy formation energies for Ni-rich compositions under the reducing synthesis conditions which match measured Ni K-edge X-ray absorption spectra. The calculated overpotential for the most active site decreases with increasing Ni content, from 0.91 V ( x = 0.33) to 0.49 V ( x = 0.66), which captures the experimentally observed trend. We find the active site changes from the Ni–O–Sb bridge to a Ni–O–Ni bridge at increasing Ni concentrations, rather than the commonly studied singly under-coordinated sites. Finally, detailed Pourbaix analysis of the identified phases show excellent electrochemical stability, consistent with experimentally measured low metal ion concentrations in the electrolyte of photoelectrochemical cells. Collectively, our consideration of an ensemble of structures enables identification of the most catalytically prolific structural motifs, aiding the understanding of crystalline and amorphous catalysts and elucidating the co-optimization of activity and durability in nickel antimonates.